Multiplex assay for detection of Bario rice samples - Yiu, Pang Hung; Lee, Huei Hong; Wong, Sie Chuong; Amartalingam, Rajan (2011)
The present invention provides a four-tube multiplex assay for distinguishing Bario rice from non-Bario rice varieties, said assay comprising the steps of running multiplex PCR with sample using one or more loci of Table 1 and distinguishing the Bario rice from non-Bario rice varieties on the basis of varietal specific multiplex allele profile. The present invention also provides a kit for performing multiplex assay for distinguishing Bario rice from non-Bario rice varieties, which may comprise primers directed to SSR loci, appropriate reagents for PCR and a control DNA template of Bario rice.